2019
DOI: 10.1177/1120672119886177
|View full text |Cite
|
Sign up to set email alerts
|

Inverted internal limiting membrane-flap technique to treat a full-thickness macular hole complicating idiopathic macular telangiectasia type 2

Abstract: Background/purpose: Full-thickness macular hole is a complication of idiopathic macular telangiectasia type 2 with a low surgical closure rate and a poor functional recovery. We analyze morphologic and functional outcomes after an inverted internal limiting membrane-flap technique for full-thickness macular hole complicating idiopathic macular telangiectasia type 2 using optical coherence tomography and microperimetry. Case report: A 77-year-old man presented us complaining visual impairment in the left eye (2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 31 publications
(42 reference statements)
0
9
0
Order By: Relevance
“…The inverted ILM flap technique has demonstrated a higher or similar closure rate in large MHs than the conventional ILM peeling technique, although its superiority with respect to long-term functional outcome is inconclusive. 23 , 24 , 25 Some studies suggested that the inverted ILM flap technique is effective in MH complicated by other macular pathologies, such as type 2 idiopathic macular telangiectasia 26 and dry age-related macular degeneration. 27 The inverted ILM flap technique was selected in the current case because exudative changes due to nAMD might have hampered MH closure.…”
Section: Discussionmentioning
confidence: 99%
“…The inverted ILM flap technique has demonstrated a higher or similar closure rate in large MHs than the conventional ILM peeling technique, although its superiority with respect to long-term functional outcome is inconclusive. 23 , 24 , 25 Some studies suggested that the inverted ILM flap technique is effective in MH complicated by other macular pathologies, such as type 2 idiopathic macular telangiectasia 26 and dry age-related macular degeneration. 27 The inverted ILM flap technique was selected in the current case because exudative changes due to nAMD might have hampered MH closure.…”
Section: Discussionmentioning
confidence: 99%
“…They reported a successful closure of the FTMH and an improvement of vision to 20/20. [ 13 ] However, the follow-up period was relatively short at 3 months. Thus, the outcome after a long follow-up period has still not been determined.…”
Section: Discussionmentioning
confidence: 99%
“…Sborgia et al [13] reported a single case of MacTel type 2 with an FTMH that had been treated by PPV using the inverted ILM-flap technique. They reported a successful closure of the FTMH and an improvement of vision to 20/20 [13] . However, the follow-up period was relatively short at 3 months.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations